2018
DOI: 10.1155/2018/6703052
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits in Patients with Chronic Spontaneous Urticaria: Evaluation of Food as Trigger of Symptoms Exacerbation

Abstract: Background Many patients with chronic spontaneous urticaria (CSU) identify different foods as triggers of their symptoms and frequently make dietary restrictions without enough information. Objective To explore the diet habits of CSU patients and estimate the clinical impact of the foods most frequently reported to be suspect. Methodology Patients were interrogated about their clinical history of urticaria. Skin prick test and sIgE serum were done for most frequently reported foods by patients. Food challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
12
0
5
Order By: Relevance
“…3 Alimentos ricos en histamina como pescados, quesos, bebidas alcohólicas, algunas frutas y verduras; así como aditivos y colorantes utilizados en la fabricación de alimentos pueden desencadenar agudizaciones de la UC. 7 Sánchez et al en 2018 14 informaron de una frecuencia de reacciones adversas a medicamentos de 13 % de, en su mayoría a AINE y antibióticos betalactámicos; en el presente estudio, la frecuencia fue obtenida mediante auto reporte, por lo cual esta prevalencia puede estar sobreestimada. Las reacciones adversas a alimentos se encontraron en una proporción mayor (18 %), comparada con lo reportado por Sánchez et al en 2019, 15 que fue de 1.2 %.…”
Section: Discussionunclassified
“…3 Alimentos ricos en histamina como pescados, quesos, bebidas alcohólicas, algunas frutas y verduras; así como aditivos y colorantes utilizados en la fabricación de alimentos pueden desencadenar agudizaciones de la UC. 7 Sánchez et al en 2018 14 informaron de una frecuencia de reacciones adversas a medicamentos de 13 % de, en su mayoría a AINE y antibióticos betalactámicos; en el presente estudio, la frecuencia fue obtenida mediante auto reporte, por lo cual esta prevalencia puede estar sobreestimada. Las reacciones adversas a alimentos se encontraron en una proporción mayor (18 %), comparada con lo reportado por Sánchez et al en 2019, 15 que fue de 1.2 %.…”
Section: Discussionunclassified
“…Differences in the prevalence of inducible urticaria and drug reactions have been reported in different parts of the world [24, 15, 3237], suggesting that in addition to the underlying mechanisms, other factors such as sociodemographic characteristics have to be considered as possible explanation for the discrepancies observed between the studies. Independent of the type of extrinsic trigger, we found that inducible urticaria and reactions to NSAIDs—but not to foods—are common comorbidities in patients with CSU and that self-reporting is usually sufficient to confirm associations.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the patients met this criterion so we did not exclude any patient from the challenge tests. The protocols used for challenge tests were based on those proposed in international guidelines [11, 12], with modifications described elsewhere [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also report that serum 25-hydroxyvitamin D levels are decreased in CSU patients, and that vitamin D supplementation improves the symptoms of CSU. 12,13 Numerous studies have examined the triggering or therapeutic effects of diets on CSU, related to pseudoallergens or vitamin D; 12,14 however, there have been no studies on dietary intakes of individual nutrients or foods in quality and quantity in CSU patients compared with healthy controls, The traditional Japanese diet includes high intake of rice, miso soup, sea products and fish. The dietary habits in Japan differ from those in Western countries.…”
Section: Introductionmentioning
confidence: 99%